1980
DOI: 10.1159/000260481
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Mineral Uptake in Developing Bovine Incisors

Abstract: This paper describes a stage in the development of deciduous bovine incisor enamel in which the tissue becomes extremely porous. This porosity, due apparently to a loss of matrix protein, is subsequently occluded by the acquisition of mineral in a secondary mineralisation phase. The porous zone has been demonstrated by a difference observed in the location of secondary mineral uptake per dry weight of tissue and secondary mineral uptake per volume of tissue. It appears to represent a stage of development analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This process is similar to that observed in rats (Hiller at al. 1975) and bovid (Robinson et al 1980). This process differs in some creatures (such as pigs), in which enamel may not mature until it has erupted (Kirkham et al 1988).…”
Section: An Introduction To Dentogenesismentioning
confidence: 99%
“…This process is similar to that observed in rats (Hiller at al. 1975) and bovid (Robinson et al 1980). This process differs in some creatures (such as pigs), in which enamel may not mature until it has erupted (Kirkham et al 1988).…”
Section: An Introduction To Dentogenesismentioning
confidence: 99%
“…Based on companion histological studies, they concluded that stage 1 strips were from the secretory stage of amelogenesis whereas stage 3 and 4, and possibly stage 2, strips were from the maturation stage of amelogenesis (Robinson et al, 1981b;Robinson and Kirkham, 1984a). While subsequently demonstrated to be a very powerful approach for studying enamel development in rat incisors (Robinson et al, 1977(Robinson et al, , 1979(Robinson et al, , 1982(Robinson et al, , 1983Kirkham, 1984a,b, 1985) and teeth of limited eruption (Glimcher et al, 1977;Robinson et al, 1978Robinson et al, , 1980Robinson et al, , 1981aRobinson et al, , 1988aDeutsch and Pe'er, 1982;Fincham et al, 1982;Deutsch et al, 1984;Kirkham, 1984a,b, 1985;Overall and Limeback, 1988), uncertainty remains about the exact location in a series of strips for the boundary between the secretory and maturation stages of amelogenesis (see Leblond and Warshawsky, 1979;Robinson et al, 1981b;Robinson and Kirkham, 1984a). Similarly, despite its use as a major reference point for enamel development, the location of the opaque boundary (Robinson et al, 1974(Robinson et al, , 1977(Robinson et al, , 1979(Robinson et al, , 1982(Robinson et al, , 1983Kirkham, 1984a, 1985) within the maturation stage of amelogenesis is not defined precisely at present.…”
mentioning
confidence: 99%
“…Concomitantly, blood vessels become intimately associated with, but do not invade, the enamel organ and anastomose among the papillae (Skobe, 1980). Changes within the maturation zone include rapid loss of amelogenins and a large increase in mineral content of the forming enamel (Fincham and Belcourt, 1985;Robinson et al, 1980). Since papillary cells do not form by mitotic division of progenitor cells (Kallenbach, 1972), the cytostructure and function of the existing dental follicle must be altered to form papillary cells.…”
Section: Biosynthesis Of Macromolecules By Follicle Explant Culturesmentioning
confidence: 99%